Returns to Scale, Technical Progress and Total Factor Productivity Growth in New Zealand Industries - Kevin J Fox (New Zealand Government, The Treasury, 2005)
This paper reviews and applies some recently proposed methods for separating total factor productivity (TFP) growth into contributions from technical progress and returns to scale, allowing for imperfectly competitive markets. The methods are applied to New Zealand data, using a recently available dataset on nine market-sector industries and the aggregate market sector, 1988-2002. The findings suggest that there has been little contribution from technical progress to TFP growth, but increasing returns to scale may have played a substantial role. However, the results are not statistically satisfactory for several industries, and are quite sensitive to the model used. This highlights the need for more work on both data and analysis if a better understanding is to be had of New Zealand's productivity performance.
Keywords: D24; 330; Returns to scale; technical progress; monopolistic markups